Activated Carbon as an Adsorbent for the Separation of Low-Molecular Alkyl Halides from Ground Water in the Production of Drinking-Water - A. Roebers; Th. Roncken; R. Hopman; CL de Ligny; B.G. Dekker; J. van der Laan; J.C. Kruithof (Adsorption Science & Technology)
An accurate method has been developed for the determination of the adsorption isotherm of trichloroethene on activated carbon over the concentration range 1 – 100 μg/1. This method has been applied to 18 samples of activated carbon of different types, both virgin and regenerated. All samples of activated carbon were characterized by determining the apparent density of the granular and the powdered carbon, and the Fe, Mn, Ca and Mg contents were determined for eight samples. The best way to describe the results mathematically has been investigated, and an improvement to the well-known Freundlich equation established.